2020
DOI: 10.1128/iai.00642-19
|View full text |Cite
|
Sign up to set email alerts
|

Whipworm Infection Promotes Bacterial Invasion, Intestinal Microbiota Imbalance, and Cellular Immunomodulation

Abstract: Infections with Trichuris trichiura are among the most common causes of intestinal parasitism in children worldwide, and the diagnosis is based on microscopic egg identification in the chronic phase of the infection. During parasitism, the adult worm of the trichurid nematode maintains its anterior region inserted in the intestinal mucosa, which causes serious damage and which may open access for gut microorganisms through the intestinal tissue. The immune-regulatory processes taking place during the evolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 58 publications
2
26
0
Order By: Relevance
“…(i) Bacteroides (Figure 8), for which many OTUs and the entire genus were significantly more abundant in the mice. In a previous mouse whipworm infection experiment, uninfected mice had undetectable levels of Bacteroides, but infected mice exhibited large amounts (200-egg infection in Swiss Webster outbred mice, 45 days post-infection) (Schachter et al, 2020), and Bacteroides is one of the major components of the T. muris microbiome (White et al, 2018). Here, we also identified two Bacteroides OTUs that were also significantly higher in whipworm-infected humans.…”
Section: Microbiome Taxa Associated With Infection Across Human and Micesupporting
confidence: 63%
See 2 more Smart Citations
“…(i) Bacteroides (Figure 8), for which many OTUs and the entire genus were significantly more abundant in the mice. In a previous mouse whipworm infection experiment, uninfected mice had undetectable levels of Bacteroides, but infected mice exhibited large amounts (200-egg infection in Swiss Webster outbred mice, 45 days post-infection) (Schachter et al, 2020), and Bacteroides is one of the major components of the T. muris microbiome (White et al, 2018). Here, we also identified two Bacteroides OTUs that were also significantly higher in whipworm-infected humans.…”
Section: Microbiome Taxa Associated With Infection Across Human and Micesupporting
confidence: 63%
“…(i) Escherichia/Shigella ( Figure 4 ) was represented by a single OTU in mice (species Escherichia coli Xuzhou21), but several OTUs in human. In a previous mouse whipworm infection study, Escherichia was one of just four genera significantly associated with infection (200-egg infection in Swiss Webster outbred mice, 45 days post-infection) ( Schachter et al., 2020 ), and in another, Escherichia was only detectable following infection (20-egg infection, C57BL/6 mice, 35 days post-infection) ( Holm et al., 2015 ). Here, we observed that it not only increased with infection in both mice and humans (at both the OTU and genera level), but also decreased following deworming in mice (OTU and genera levels) and humans (OTU level).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of the microbiota during helminth infection is becoming increasingly recognized, and is also the start of an exciting and crucial area of parasitological research. Microbial changes have been reported for multiple intestinal helminths including infections with Ascaris lumbricoides (Ramírez-Carrillo et al ., 2020 ), H. polygyrus (Walk et al ., 2010 ; Kreisinger et al , 2015 ), Necator americanus (hookworm; Cantacessi et al ., 2014 ) and of interest for this review T. trichiura (Lee et al ., 2014 ; Chen et al ., 2021 ) and T. muris (Holm et al ., 2015 ; Houlden et al ., 2015 ; Schachter et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a well-established model of chronic worm infection, when laboratory wild-type mice are given a single low dose of embryonated eggs (20–30 T. muris eggs) upon transition from larvae to adult worms (day 28 post infection), the gut microbiota undergo compositional changes (Houlden et al ., 2015 ; Schachter et al ., 2020 ). Specifically, bacterial taxa like Firmicutes , Mucispirillum and Proteobacteria increase as a result of infection; whilst Parabacteroides and Prevotella decrease in abundance (Holm et al ., 2015 ; Houlden et al ., 2015 ; Schachter et al ., 2020 ). The observed changes in microbial composition from infection appear to be parasite-dependent and transient in nature.…”
Section: Helminth-microbe Interactionsmentioning
confidence: 99%